Efektivitas Pengaruh Lingkungan Terhadap Korban Bullying Berdasarkan Perspektif Kriminologi Dalam Ranah Pendidikan - Alfatir, Muhammad Nur; Akbar, Raehan; Nathanael, Kristian; Najma, Siti Najla Nur; Nugraha, Setyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Bullying is not a new criminal act in society. Bullying cannot be underestimated considering that the impact of bullying is the most dangerous, namely that it can cause someone to have the desire to commit suicide. Therefore, there is a need for protection and an approach provided by law so that the crime of bullying in Indonesia can be reduced. This article was created to find out what factors cause bullying to occur, as well as the effectiveness of the environment on victims of bullying. Based on the research results, answers to existing problems can be obtained and conclusions can be drawn, firstly, bullying treatment that occurs in the educational environment can be seen from two aspects, namely the perpetrator and the victim. Judging from the perpetrator's perspective, there are racial differences, the appearance of symbols of seniority, the nature of feeling perfect, broken homes (problems in the family), as a means of entertainment, increasing popularity, and economic differences. The factors viewed from the victim's perspective are that the victim is weaker, keeps quiet a lot, and is a new person in their environment. Second, if there is an act of bullying violence in positive law, it is subject to the law in the Criminal Code.